Adaptive automation assembly: Identifying system requirements for technical efficiency and worker satisfaction - Fletcher, Sarah R.; Johnson, Teegan L.; Adlon, Tobias; Larreina, Jon; Casla, Patricia; Parigot, Laure; Alfaro, Pedro J.; Del Mar Otero, María (Elsevier, 2019)
Manual assembly work systems bring high flexibility but low productivity in comparison to fully automated systems. To increase productivity but maintain flexibility, future systems need to incorporate greater levels of automation which complement or augment the capabilities of the human operators who provide the manual work. Future systems should be designed for social and economic sustainability within fluctuating conditions and for adaptive utilisation of operators’ individual capabilities to maintain levels of productivity and personal satisfaction. To successfully create such systems with greater adaptivity and interactivity between people and technology a comprehensive understanding of design requirements is needed; the current problem is that there is no standard valid framework. The work described in this paper employed a three-component investigation to identify the various key requirements that are needed to form such a design framework for future human-automation assembly systems. This involves separate activities with different methodologies involving literature reviews, surveys and business case analysis to define use case scenarios and requirements for creating adaptive automation assembly system demonstrators. The different methodological approaches and results for all of the three component studies are described, along with conclusions and implications for further research work and for industry in general.
Keywords: Adaptive workplaces; Automation; Human-robot collaboration; Interaction mechanisms; Worker satisfaction; Assembly; Flexible production